D2, D3 lymph node dissection importance in colon cancer surgery - E. A. Dzhenkova; E. A. Mirzoyan; A. A. Maslov; Yu. A. Gevorkyan; D. A. Kharagezov; A. G. Milakin; O. N. Stateshniy; O. Yu. Kaymakchi; A. V. Dashkov; G. V. Kaminskiy; V. E. Kolesnikov; S. A. Malinin; et al. (Южно-Российский онкологический журнал)
Colorectal cancer (CRC) is a relevant issue of modern oncology and ranks the third place among most common malignancies. Every year, more than 1 million new cases of CRC are diagnosed worldwide, with approximately the same frequency of prevalence among the male and female population. Colon cancer (CC) amounts for more than half of all cases of CRC, and it’s incidence and mortality remain rather high.Surgery remains the main method of CRC treatment, and determining the extent of surgery and lymph node dissection remains an urgent problem.For the first time in Japan, a classification of groups of lymph nodes (l.n.) was proposed depending on the level of lymph outflow and location in relation to the main vessels. According to the numbering of l.n. groups by the Japanese Society for Cancer of the Colon and Rectum (JSCCR), all lymph nodes are numbered with three digits.As a rule, lymphogenic metastasis occurs in one direction, bilateral spread is possible if the tumor is located at the same distance from two feeding vessels. With tumors of the right-sided localization, all groups of l.n. located along the branches of the superior mesenteric artery are removed, and with tumors of the left half of the colon, all l.n. located along the trunk of the inferior mesenteric artery are removed. The presence of affected l.n. is important for assessing the prognosis and further determining the need for adjuvant therapy. Some literature data demonstrate good results of surgical interventions performed in accordance with the concept of embryonic planes and complete mesocolonic excision. D3 lymph node dissection is not performed in daily practice in some European countries and North America, unlike a number of Eastern countries. However, the level of vessel ligation remains the subject of scientific discussion.The purpose of this review was to analyze the available literature on the problem of choosing the level of lymph node dissection in CC surgery.